2022
DOI: 10.3389/fimmu.2022.1080403
|View full text |Cite
|
Sign up to set email alerts
|

Integration analysis identifies MYBL1 as a novel immunotherapy biomarker affecting the immune microenvironment in clear cell renal cell carcinoma: Evidence based on machine learning and experiments

Abstract: BackgroundPrevious studies have identified MYBL1 as a cancer-promoting molecule in numerous types of cancer. Nevertheless, the role of MYBL in renal cancer remains unclear.MethodsGenomic and clinical data of clear cell renal cell carcinoma (ccRCC) was get from the Cancer Genome Atlas (TCGA) database. CCK8, colony formation, and 5-ethynyl-2’-deoxyuridine assay were utilized to evaluate the performance of cell proliferation. Cell apoptosis was detected using the flow cytometric analysis. The protein level of MYB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Other studies show over-expression of MYBL1 in low-grade glioma [8], breast adenoid cystic carcinoma, which is a rare triple-negative cancer with a good prognosis [9] and tracheobronchial adenoid cystic carcinoma [10]. Wang et al suggest the use of MYBL1 as an immunotherapy biomarker in clear cell renal cell carcinoma [11], and our data show that some TNBCs express high levels of the MYBL1 gene [12]. Related to structural changes in the gene, Fujii et al identified genomic rearrangements and gene fusions of MYBL1 with ACTN1, AFIB and NFIB genes [13] in adenoid cystic carcinoma tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show over-expression of MYBL1 in low-grade glioma [8], breast adenoid cystic carcinoma, which is a rare triple-negative cancer with a good prognosis [9] and tracheobronchial adenoid cystic carcinoma [10]. Wang et al suggest the use of MYBL1 as an immunotherapy biomarker in clear cell renal cell carcinoma [11], and our data show that some TNBCs express high levels of the MYBL1 gene [12]. Related to structural changes in the gene, Fujii et al identified genomic rearrangements and gene fusions of MYBL1 with ACTN1, AFIB and NFIB genes [13] in adenoid cystic carcinoma tumors.…”
Section: Introductionmentioning
confidence: 99%